Christian Punk: identity and performance (Bloomsbury studies in religion and popular music, 2020)
"Christian punk is a surprisingly successful musical subculture and a fascinating expression of American evangelicalism. Situating Christian punk within the modern history of Christianity and the rapidly changing culture of spirituality and secularity, this book illustrates how Christian punk continues punk's autonomous and oppositional creative practices, but from within a typically traditional evangelical morality. Analyzing straight edge Christian abstinence and punk-friendly churches, this book also focuses on gender performance within a subculture dominated by young men in a time of contested gender roles and ideologies. Critically-minded and rich in ethnographic data and insider perspectives, Christian Punk will engage scholars of contemporary evangelicalism, religion and popular music, and punk and all its related subcultures."--